Analisis Penerapan Akuntansi Lingkungan Terhadap Pengelolaan Limbah (Studi Kasus Pada PT Perkebunan Nusantara VII Lampung Tengah) - Tri Herlinda; Natasya Adelia putri; Nasrul Kahfi (Jurnal Riset Akuntansi, 2024)
The purpose of this study is to evaluate how a company identifies, recognizes, measures, presents, and discloses in its financial statements the environmental accounting aspects related to waste treatment costs. This research uses a descriptive approach and document analysis to explore the role of environmental accounting on waste management through the collection and evaluation of related documents. The researcher's findings are the application of accounting to the environment of PT Perkebunan Nusantara VII Bekri Lampung Central Unit records the transaction as an expense if it is used for the company's operational activities. Environmental Accounting Applied to Waste Management at PT Perkebunan Nusantara VII Bekri Central Lampung Unit using the checklist method and has 100% means it meets the standards.